图像处理技术在齿轮缺陷检测中的应用 - 肖俊建; 王慧英 (Jixie chuandong)
To deal with the defet of gear,the identification technology is studied.Applied with image forming、 edge detection、image transform、median filter、threshold segmentation、edge detection、 feature extraction、 pattern recognition,the method of threshold construction and the edge extraction algorithm are proposed.Lastly,the method of automatic identification technology of defects of gear is obtained.Advanced image processing technology is an effective method of controlling product quality and fault diagnosis.